2014
DOI: 10.1093/ageing/afu173
|View full text |Cite
|
Sign up to set email alerts
|

Preventing delirium: should non-pharmacological, multicomponent interventions be used? A systematic review and meta-analysis of the literature

Abstract: Multicomponent interventions are effective in preventing incident delirium among elderly inpatients. Effects seemed to be stable among different settings. Due to the limited amount of data, potential benefits in survival need to be confirmed in further studies. Future research should be aimed at contrasting different multicomponent programmes to select the most useful interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
0
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(126 citation statements)
references
References 38 publications
10
108
0
8
Order By: Relevance
“…Although our preliminary outcomes need to be confirmed in a larger, randomized trial, which is planned to be performed, the results are comparable to those presented in the recent meta-analysis by Martinez et al Martinez and colleagues pooled 3 studies with a total number of 582 patients [19, 20, 23] and a nonsignificant reduction in in-hospital mortality was observed [8]. Among these, only Vidán et al's study found a statistically significant increase in preventing in-hospital deaths for patients allocated to the intervention [23].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although our preliminary outcomes need to be confirmed in a larger, randomized trial, which is planned to be performed, the results are comparable to those presented in the recent meta-analysis by Martinez et al Martinez and colleagues pooled 3 studies with a total number of 582 patients [19, 20, 23] and a nonsignificant reduction in in-hospital mortality was observed [8]. Among these, only Vidán et al's study found a statistically significant increase in preventing in-hospital deaths for patients allocated to the intervention [23].…”
Section: Discussionsupporting
confidence: 79%
“…Most importantly, at least 30% to 40% of cases of delirium are potentially preventable [6, 7]. Currently, there is no rationale for pharmacological prophylaxis of delirium, whereas nonpharmacological interventions are widely supported by growing evidence from clinical trials, systematic reviews, and meta-analyses [810]. Delirium usually has a multifactorial etiology.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of 14 interventional studies based on the Hospital Elder Life Program, 57,58 these approaches significantly reduced the risk of incident delirium by 53% (odds ratio, 0.47 [95% CI, 0.38–0.58]), and the risk of falls by 62% (odds ratio, 0.38 [95% CI, 0.25–0.60]) among hospitalized, non-ICU patients 65 years and older. 22 …”
Section: Resultsmentioning
confidence: 99%
“…Demographic and physical factors are age, gender, hospitalized days, institutionalization, trauma history, surgery, heart and lung illness, hypertension, diabetes, chronic kidney failure, gastrointestinal diseases, urinary and genital illness, metabolic disorders, central nervous system illness, peripheral vascular disease, stroke, dementia, malnutrition, fever, low albumin, low oxygen, dehydration, electronic imbalance, azotemia, infection, convulsion, and multiple or pain medications [1,2,4,5,[7][8][9][11][12][13][14][15][16][17][18]. Specifically, 3% to 5% of elderly people who have had hip and knee surgeries would experience acute confusion or delirium for a specific period.…”
Section: Related Factors Of Elderly Deliriummentioning
confidence: 99%
“…Moreover, delaying the time of delirium might increase the incidence of illness, patients' dependence, the needs of nursing homes, and death rates because of the heavy burden on the health care system and society [1,4,5,7,9,10,14,16,18,19]. In addition, a study reported that urinary tract infection (UTI) rates in elderly patients with delirium ranged from 25.9% to 32% compared with 13% in those without delirium; in patients with UTI, delirium rates ranged from 30% to 35%, compared with 7.7% to 8% in those without UTI [11].…”
Section: Consequences Of Elderly Deliriummentioning
confidence: 99%